SOA Security L the only thing we have to fear is fear itself. - Epstein, Jeremy (SOA webservices journal.)
"Let me assert my firm belief that the only thing we have to fear is fear itself-nameless, unreasoning, unjustified terror, which paralyzes needed efforts to convert retreat into advance." - Franklin Delano Roosevelt